PERLINDUNGAN DAN PENGELOLAAN BUDAYA LOKAL DI KOTA YOGYAKARTA - Dyah Permata (Kajian Hukum, 2016)
Merti Code  is one of the local culture that has a high value in the philosophical field of environmental preservation in the city of Yogyakarta, which should be preserved . Values contained in the Merti Code local culture is very noble, because Merti Code is an activity for "memerti" ( maintain ) the river environment , so that the balance of the river ecosystem to be awake . It is rarely done by people in the modern city today . Merti Code is maintained by the local cultural communities in Bantaran  Kali Code, but it also has the distinctive feature of the ceremony held each year and the tourism event in the city of Yogyakarta . For that we need a proactive attitude of the local government to protect aspects of folklore in the city of Yogyakarta, which is an asset for tourism in Yogyakarta considerable potential. Protection do not only cover the legal protection , but from non aspect law can also be given protection, in addition to fixing the Tourism Regulation relating to the follow-up to the local culture in Yogyakarta, for non-law asepek can be done with the inventory process, documentation and abstraction of the local culture . The next step is to make an agreement between the custodian Benefit Sharing with third parties that take advantage of the wealth of local culture .